2011
DOI: 10.1186/1465-9921-12-29
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterisation of pulmonary and serum surfactant protein D in COPD

Abstract: BackgroundPulmonary surfactant protein D (SP-D) is considered as a candidate biomarker for the functional integrity of the lung and for disease progression, which can be detected in serum. The origin of SP-D in serum and how serum concentrations are related to pulmonary concentrations under inflammatory conditions is still unclear.MethodsIn a cross-sectional study comprising non-smokers (n = 10), young - (n = 10), elderly smokers (n = 20), and smokers with COPD (n = 20) we simultaneously analysed pulmonary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
103
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 32 publications
14
103
2
2
Order By: Relevance
“…However, the ECLIPSE investigator failed to find a significant relationship between FEV1% predicted and SP-D in COPD patients [24]. In spite of that, our findings were in line with those of Sin et al [28] who showed an inverse correlation between circulating SP-D and FEV1 in COPD patients and those with Winkler et al [29], who found an inverse correlation of SP-D levels with FEV1/FVC in COPD. Consistently, we observed a positive correlation between serum SP-D with MDA and PC in patients with COPD.…”
Section: Discussionsupporting
confidence: 89%
“…However, the ECLIPSE investigator failed to find a significant relationship between FEV1% predicted and SP-D in COPD patients [24]. In spite of that, our findings were in line with those of Sin et al [28] who showed an inverse correlation between circulating SP-D and FEV1 in COPD patients and those with Winkler et al [29], who found an inverse correlation of SP-D levels with FEV1/FVC in COPD. Consistently, we observed a positive correlation between serum SP-D with MDA and PC in patients with COPD.…”
Section: Discussionsupporting
confidence: 89%
“…Reminiscent of findings in this study, targeted deletion of the pulmonary collectins SP-A and SP-D has been shown to promote airway inflammation (1,34) by enhancing alveolar macrophage activation (10,15). Interestingly, the type of immune modulatory response induced by these proteins is influenced by the binding orientation of SP-A or SP-D on alveolar macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, a significant positive correlation was observed between BALF SP-D levels and respiratory function (FEV 1 /FVC). 26,28) In our study, stimulation of PPARβ/δ by GW0742 increased the expression of SP-D in lung tissue and improved FEV 0.05/FVC in emphysema model mice.…”
Section: Discussionsupporting
confidence: 55%